A first-in-human clinical study of a new SP-B and SP-C enriched synthetic surfactant (CHF5633) in preterm babies with respiratory distress syndrome. Issue 6 (2nd May 2017) - Sweet, David G; Turner, Mark A; Straňák, Zbyněk; Plavka, Richard; Clarke, Paul; Stenson, Ben J; Singer, Dominique; Goelz, Rangmar; Fabbri, Laura; Varoli, Guido; Piccinno, Annalisa; Santoro, Debora; et al.
Abstract : Objective: CHF5633 (Chiesi Farmaceutici S.p.A., Parma, Italy) is the first fully synthetic surfactant enriched by peptide analogues of two human surfactant proteins. We planned to assess safety and tolerability of CHF5633 and explore preliminary efficacy. Design: Multicentre cohort study. Patients: Forty infants from 27 +0 to 33 +6 weeks gestation with respiratory distress syndrome requiring fraction of inspired oxygen (FiO2 ) ≥0.35 were treated with a single dose of CHF5633 within 48 hours after birth. The first 20 received 100 mg/kg and the second 20 received 200 mg/kg. Outcome measures: Adverse events (AEs) and adverse drug reactions (ADRs) were monitored with complications of prematurity considered AEs if occurring after dosing. Systemic absorption and immunogenicity were assessed. Efficacy was assessed by change in FiO2 after dosing and need for poractant-alfa rescue. Results: Rapid and sustained improvements in FiO2 were observed in 39 (98%) infants. One responded neither to CHF5633 nor two poractant-alfa doses. A total of 79 AEs were experienced by 19 infants in the 100 mg/kg cohort and 53 AEs by 20 infants in the 200 mg/kg cohort. Most AEs were expected complications of prematurity. Two unrelated serious AEs occurred in the second cohort. One infant died of necrotising enterocolitis and another developed viral bronchiolitis after discharge. The single ADR was an episode of transient endotracheal tube obstruction following a 200 mg/kg dose. Neither systemic absorption, nor antibody development to either peptide was detected. Conclusions: Both CHF5633 doses were well tolerated and showed promising clinical efficacy profile. These encouraging data provide a basis for ongoing randomised controlled trials. Trial registration number: ClinicalTrials.gov NCT01651637 .